Route diversity analyses for free-space optical wireless links within turbulent scenarios - Zvanovec, Stanislav; Perez, Joaquin; Ghassemlooy, Zabih; Rajbhandari, Sujan; Libich, Jiri (Optics express, 2013)
Free-Space Optical (FSO) communications link performance is highly affected when propagating through the time-spatially variable turbulent environment. In order to improve signal reception, several mitigation techniques have been proposed and analytically investigated. This paper presents experimental results for the route diversity technique evaluations for a specific case when several diversity links intersects a common turbulent area and concurrently each passing regions with different turbulence flows.
Keywords: optické prostředky; Computer Simulation; Telecommunications; Light; bezdrátová technologie; radiační rozptyl; teoretické modely; světlo; Optical Devices; telekomunikace; Models, Theoretical; počítačová simulace; Scattering, Radiation; Wireless Technology